Moyamoya disease: a case report - Sehgal, Parul; Wasim, Sanober (International Journal of Contemporary Pediatrics, 2018)
Moyamoya disease is a chronic, progressive occlusion of the circle of Willis arteries that leads to the development of characteristic collateral vessels seen on cerebral angiography. The appearance of these small, multiple vessels at the base of the brain resembles “puff of smoke”. The disease may develop in children and adults, but the clinical features differ. Children are likely to suffer with ischemic or haemorrhagic stroke. In the present report, authors describe a 7-year-old female with history of recurrent stroke apraxia and atrophy of left side with facial nerve palsy and was later on diagnosed with Moyamoya disease at HIMS Dehradun. Conclusion: Child with Moyamoya disease presents with recurrent episodes of sudden hemiplegia that might occur on alternate sides. The disease is progressive and dynamic in children. MRA clinches the diagnosis and neurosurgical intervention may be required as a part of definitive management.